Linking Education and Business across Geography of Erasmus +Improving Relationships between Vocational Training and Job Market - Balaguer, Pedro Antonio (Journal of Entrepreneurship, Business and Economics; Vol 4 No 1 (2016), 2016)
A multitude of studies have demonstrated that entrepreneurial competence is not only required to start an enterprise but it is a key lifelong learning competence relevant for the labour market. The recent communications of the European Commission however underlines the need for more entrepreneurs-hip education in Europe. The following paper describes a novel approach to training of entrepreneu-rial skills, which has been developed by the European funded project Linking Education and Business (LEB) (www.oai.ie/linking-education-business.php). The project team, which consists of VET scho-ols and enterprises, focuses on the new dynamics of society, which is demanding not only individuals with critical thinking and ethics training to contribute to sustainable development, but also with strong capabilities to survive in an increasingly demanding job market. The gap between the labor market and the education system generates controversy among experts about how to fix it, being necessary to try to solve the above deficiencies and respond to the new challenges of the production system in a new economic and social contexts. Research paper Reference to this paper should be made as follows: Balaguer, P. A. (2016). “Linking Education and Business across Geography of Erasmus +. Improving Relationships between Vocational Training and Job Market”, Journal of Entrepreneurship, Business and Economics, Vol. 4, No. 1, pp. 73–84.